INTERROGATING ISLAMIC LAW AND POSITIVE LAW AGAINST COUNTERFEIT PRODUCTS IN THE CONSUMER SOCIETY - Iva Faizah; Zulfa Ahmad Kurniawan (UIN Kiai Haji Achmad Siddiq Jember, 2022)
Counterfeit goods or what we know as KW goods, that goods with low quality are buying and selling commodities that are very profitable. The fact that Indonesians are known as consumptive people, driven by a large number of Indonesians, the development of technology that facilitates transaction access, and the emergence of various marketplaces that provide counterfeit products are factors that make it easier for people to get the desired counterfeit product. The ease of getting product with the same quality as the original product but have a minimal price is an advantage for the transaction, but that transaction also brings losses, especially for the owner of patent rights on the trademarks of the products being traded, on the condition that the loss is legally violated and provides criminal penalties and fines for the perpetrators, as well as in the point of view of Islamic law. Literatur study is used as a research method used to examine in depth the views of Islamic law and positive law on buying and selling counterfeit products. The results of the analysis state that intellectual property rights in the form of patents, trademarks, copyrights, and so on are seen as one of the huquq maliyyah (property rights) which has legal protection (mashun) like mal (worth) than someone who consciously uses or transacts counterfeit products (KW) on patents, trademarks, copyrights, etc. illegally has committed an injustice and this action is unlawful